ROLE OF BOARD COMPOSITION ON VOLUNTARY CYBERSECURITY DISCLOSURE: EVIDENCE OF BANKING COMPANIES IN SOUTHEAST ASIA - Ain, Naougy Hurun; Fernando, Kenny; Kurniawan, Budi; Sambuaga, Elfina Astrella (Akuntabilitas, 2023)
This study aims to examine the correlation between board composition and cybersecurity disclosure (CSD) in Southeast Asia banking companies, while  investigating the influence of financial characteristics such as profitability, leverage, and firm size on CSD practices. The quantitative analysis methodology is employed in this paper. The level of cybersecurity disclosure in annual reports is analyzed using content analysis with 54 keywords, analyzed through NVIVO 14 software. The correlation between variables is examined using STATA Software with panel data comprising 391 observations. The study focuses on 101 Southeast Asia banking companies from 2017 to 2021. The results indicate that only firm size, measured by the natural logarithm of total assets, has a positive and significant influence on CSD. This suggests that larger firms with higher total assets are more likely to voluntarily disclose cybersecurity information in their annual reports. No statistically significant correlation is found between board composition, other financial factors, and CSD during the study period. This paper acknowledges its limitations and proposes directions for future research. Firstly, the study is limited to listed commercial banks. Future research should include a larger sample encompassing non-financial industry firms. Secondly, the study employs automated content analysis, specifically counting keywords, to assess the quantity of CSD. Future research could conduct discourse analysis of CSD narratives to provide a more meaningful analysis. This approach would evaluate whether the language and tone of CSD convey substantial information to stakeholders or if it is merely a standardized practice. Additionally, future research should explore other variables impacting voluntary CSD and examine economic consequences, such as the effect on the cost of capital. The findings have implications for regulators, policymakers, and companies, enabling regulators to better understand the current level of CSD and determine the need for further guidance.